Pengembangan Floating Constructed Wetland Skala Laboratorium sebagai Reduktor Kandungan Kontaminan Limbah Domestik Badan Air Perkotaan - Prastica, Rian Mantasa Salve; Sulaiman, Muhammad (MEDIA KOMUNIKASI TEKNIK SIPIL, 2021)
Low awareness of sanitation of urban citizens creates negative effects on the environment which varied. The triggering factors of the phenomenon are education and conservation technology. A conservation technology, eco-technology e.g. constructed wetlands, is proposed to solve the problem. Laboratory work is conducted to obtain comprehensive analysis about floating constructed wetland. The research paper aims to illustrate the efficiency performance of constructed wetlands, with domestic species, in the lab-scaled area from urban wastewater. The constructed wetland media is prepared horizontally. The analysis of its performance leads to a discussion of urban water quality. Samplings and laboratory tests are conducted to examine pH, phosphorus, nitrogen, suspended solids, conductivity, COD, and BOD. The benefit of Nasturtium officinale as FTW media reduce phosphate, nitrate, and BOD as 100% in 14 days. The discharge simulation during 14 days reduce TDS and TSS as 100%.